Acute Ischemic Stroke Hospital Admissions, Treatment, and Outcomes in Poland in 2009–2013 - Chwojnicki, Kamil; Ryglewicz, Danuta; Wojtyniak, Bogdan; Zagożdżon, Paweł; Członkowska, Anna; Jędrzejczyk, Tadeusz; Karaszewski, Bartosz; Kozera, Grzegorz; Gierlotka, Marek; Ezzati, Majid; Zdrojewski, Tomasz (Frontiers in Neurology, 2018)
Introduction: Ischemic stroke (IS) still constitutes a serious problem for public health worldwide. The data on its burden in Poland before 2009 is limited and came only from a few metropolitan areas. The aims of the study were: to assess temporal trends in the hospital admissions, treatment and outcomes of IS in Poland in 2009-2013, to identify risk factors for IS mortality and to compare the results with other countries. Methods: The data from the Polish Stroke Registry was analyzed. The data concerned all subjects hospitalized due to IS (classified according to the ICD10 classification as I63.0-I63.9) as primary diagnosis in Poland in 2009-2013. Temporal trends in treatment and outcome were analysed. Hospital admissions rates as well as case fatality and 12-months mortality rates were calculated. Results: Altogether 360,556 patients (47.5% of males) were hospitalized due to IS in Poland in 2009–2013. The median of age was 75 years, IQR 18 (Women 78, IQR 14 vs Men 70, IQR 17; p<0.001). The hospital admissions age-standardized annual rate for IS in Poland in 2013 was 8% lower than in 2009 (169 vs. 157/100,000; p for trend<0,001). In-hospital case fatality has slightly decreased (from 13.6% in 2009 to 12.9% in 2013; p for trend<0.001) . One-year post-hospital mortality rate has not changed (19.3% in 2009 and 2013). The percentage of IS subjects treated with intravenous thrombolysis was low but increased from 1.7% in 2009 to 6.3% in 2013 (p for trend<0.001). Conclusions: Since 2009, Poland has had national epidemiological data on the hospital admissions, treatment and outcomes in IS. The data indicate a slow improvement of in-hospital survival and suggest the need for better stroke prevention and further dissemination of reperfusion therapy.